Youth Labour Market in Romania’s Development Regions in the Framework of Sustainable Development and of a Knowledge-based Economy - Bălan, Mariana (Studia Universitatis Vasile Goldiș Arad, Seria Științe Economice, 2017)
Even if the issue of youths‘ inclusion in the labour market was always an important item on political agendas, during the last two decades this issue had particular relevance. In the last years, unemployment for this age group had unprecedented amplitude, reaching 20.6% in Romania in 2016. Modern societies provide for youths opportunities, still they are faced with major challenges related to the education and training and access to the labour force market. During the last decades, the world economy shifted in a continuous process from development based on traditional factors to the knowledge-based economy. The development of the knowledge-based economy leads to changes in labour force demand also: new skills and competences are required. As new technologies are implemented, the demand for high-skilled workers increases, especially for high-skilled ones in the field of Information and Communication (IC), and the demand for low-skilled workers decreases. The paper presents a brief characterisation of the labour force market at the level of Romania‘s regions of development and an analysis of the particularities of the youths‘ labour market in the context of sustainable development and of the new economy as well as some advantages of using young labour force for sustainable development.